Thickness-Induced Metal-Insulator Transition in Sb-doped SnO2 Ultrathin Films: The Role of Quantum Confinement - Ke, Chang (2015)
A thickness induced metal-insulator transition (MIT) was firstly observed in Sb-doped SnO2 (SnO2:Sb) epitaxial ultrathin films deposited on sapphire substrates by pulsed laser deposition. Both electrical and spectroscopic studies provide clear evidence of a critical thickness for the metallic conductivity in SnO2:Sb thin films and the oxidation state transition of the impurity element Sb. With the shrinkage of film thickness, the broadening of the energy band gap as well as the enhancement of the impurity activation energy was studied and attributed to the quantum confinement effect. Based on the scenario of impurity level pinning and band gap broadening in quantum confined nanostructures, we proposed a generalized energy diagram to understand the thickness induced MIT in the SnO2:Sb system.